Genome Sequences of Three Frequently Used Listeria monocytogenes and Listeria ivanovii Strains - Klumpp, Jochen (American Society for Microbiology, 2014)
We present the complete de novo assembled genome sequences of Listeria monocytogenes strains WSLC 1001 (ATCC 19112) and WSLC 1042 (ATCC 23074) and Listeria ivanovii WSLC 3009, three strains frequently used for the propagation and study of bacteriophages because they are presumed to be free of inducible prophages.